Propuesta de la creación de ventaja competitiva en la Empresa de Construcción Anclatech SAS, a través de la planeación estratégica en Bogotá, D.C. (2023)
The following document has the purpose of identifying weaknesses, aspects to improve and generating milestones that will provide the basis for the implementation of the strategic planning guide. The aforementioned aspects will be addressed through 3 specific objectives that will be: The first is the identification of the micro and macro environment of the company through the matrices and graphs that will provide us with information about where the company's shortcomings are, Then comes the analysis of the results and taking them to tables that show or subtract the areas to improve.